Developing Border Gate Economic Zones: Current Situations and Proposed Solutions - Hung, Le Tuan (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2019)
The development of border gate economic zones is not only an important driving force for economic development in border areas but also contributes to the national economic development. In this paper, the development is viewed in the way that it does not indicate a need for a rapid increase in the number of economic zones but rather an improvement of quality of economic activities in the border gate economic zones. This paper analyzes the conditions and content of the border gate economic zone development, introducing models of border gate economic zones that can be applied, thereby suggesting solutions to promote the development of Vietnam's border gate economic zones in the future.